About reptiles : a guide for children - Sill, Cathryn P. 1953-; Sill, John (Atlanta : Peachtree, 1999)
Depicts how physical characteristics, habitat, movement, feeding and hunting behavior, and life cycle can vary in different kinds of reptiles, including the corn snake, eastern box turtle, and American alligator.
H
460
H
Keywords: Reptiles -- Juvenile literature; Reptiles